Technetium-99m chelator-free radiolabeling of specific glutamine tumor imaging nanoprobe: in vitro and in vivo evaluations - Ghoreishi SM (Dove Medical Press, 2018)
Seyedeh Masoumeh Ghoreishi,1,2 Ali Khalaj,1 Omid Sabzevari,3 Leila Badrzadeh,1 Pardis Mohammadzadeh,1,4 Seyed Shahaboddin Mousavi Motlagh,5 Ahmad Bitarafan-Rajabi,6 Mehdi Shafiee Ardestani1 1Department of Radiopharmacy, Faculty of Pharmacy, Tehran University of Medical Sciences, Tehran, Iran; 2Cancer Research Center, Health Research Institute, Babol University of Medical Sciences, Babol, Iran; 3Department of Toxicology and Pharmacology, Faculty of Pharmacy, Toxicology and Poisoning Research Centre, Tehran University of Medical Sciences, Tehran, Iran; 4Department of Genetics and Molecular Biology, Isfahan University of Medical Sciences, Isfahan, Iran; 5Biotechnology Department of Iranian Food and Drug Administration, Ministry of Health, Tehran, Iran; 6Echocardiography Research Center, Cardiovascular Interventional Research Center, Department of Nuclear Medicine, Rajaie Cardiovascular Medical and Research Center, Iran University of Medical Sciences, Tehran, Iran Introduction: Nowadays, molecular imaging radiopharmaceuticals’, nanoparticles’, and/or small-molecule biomarkers’ applications are increasing rapidly worldwide. Thus, researchers focus on providing the novel, safe, and cost-effective ones. Materials and methods: In the present experiment, technetium-99m (99mTc)-labeled PEG-citrate dendrimer-G2 conjugated with glutamine (nanoconjugate) was designed and assessed as a novel tumor imaging probe both in vitro and in vivo. Nanoconjugate was synthesized and the synthesis was confirmed by Fourier transform infrared, proton nuclear magnetic resonance, liquid chromatography-mass spectrometry, dynamic light scattering, and static light scattering techniques. The toxicity was assessed by XTT and apoptosis and necrosis methods. Results: Radiochemical purity indicates that the anionic dendrimer has a very high potential to complex formation with 99mTc and is also very stable in the human serum in different times. Results from the imaging procedures showed potential ability of nanoconjugates to detect tumor site. Conclusion: Suitable features of the anionic dendrimer show that it is a promising agent to improve nanoradiopharmaceuticals. Keywords: biodegradable, biocompatible, dendrimer, glutamine, chelator free, radiolabeling